2012
DOI: 10.1109/ted.2012.2222414
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ionizing Radiation on the $\hbox{SiO}_{2}/ \hbox{SiC}$ Interface in 4H-SiC BJTs

Abstract: Degradation of SiO 2 surface passivation for 4H-SiC power bipolar junction transistors (BJTs) as a result of ion irradiation has been studied to assess the radiation hardness of these devices. Fully functional BJTs with 2700 V breakdown voltage are implanted with 600 keV helium ions at fluences ranging from 1 × 10 12 to 1 × 10 16 cm −2 at room temperature. These ions are estimated to reach the SiO 2 /SiC interface. The current-voltage characteristics before and after irradiation show that the current gain of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been observed previously that the deposition of Al 2 O 3 by using ALD results in huge shift in flatband voltage (V BE ) and, normally, a post deposition treatment is required to reduce this shift. 17,18 However, here in the stacked dielectrics, consisting of HfO 2 and Al 2 O 3 , it is observed that RTA has considerably increased the total amount of fixed charges in the oxide. The fixed charge in the oxide, observed in CV measurements, has a contribution from the distribution of charges in the whole oxide layer, as well as from the interface between HfO 2 /Al 2 O 3 and the interface between Al 2 O 3 /SiC.…”
Section: Resultsmentioning
confidence: 85%
“…It has been observed previously that the deposition of Al 2 O 3 by using ALD results in huge shift in flatband voltage (V BE ) and, normally, a post deposition treatment is required to reduce this shift. 17,18 However, here in the stacked dielectrics, consisting of HfO 2 and Al 2 O 3 , it is observed that RTA has considerably increased the total amount of fixed charges in the oxide. The fixed charge in the oxide, observed in CV measurements, has a contribution from the distribution of charges in the whole oxide layer, as well as from the interface between HfO 2 /Al 2 O 3 and the interface between Al 2 O 3 /SiC.…”
Section: Resultsmentioning
confidence: 85%
“…doping of p-shield 5×10 18 The key device parameters of the following investigations are shown in Table 1, and these devices' drift parameters are designed for 15-kV voltage level according to Sung et al [16] The thickness of sidewall and bottom of gate oxide is 50 nm and 100 nm, respectively. The mobility of MOSchannel is set to be 30 cm 2 /V•s.…”
Section: Device Mechanism and Descriptionmentioning
confidence: 99%
“…where L a is the am-bipolar diffusion length. Because the doping concentration of the N-drift region can affect carrier mobility 2) and carrier lifetime, [26][27][28] L a is dependent on the doping concentration of the N-drift region. The hole-carrier concentration at P + collector=N-buffer ( p 0 ) 23) and P + shield-ing=N-drift ( p WB ) can be written as…”
Section: Hole-carrier Concentration Profilementioning
confidence: 99%